An assessment of small islands coral cover and coral-reef fish diversity at Oba Sub-district, Halmahera Island. Issue 1 (October 2021) - Ismail, F; Akbar, N; Tahir, I; Paembonan, R E; Marus, I; Wibowo, E S
Abstract: Study on the percentage of coral cover four small islands of Oba Sub-district, Halmahera Island of North Maluku Utara Province was carried out in April 2021.The four small islands of Oba Sub-district studied are Woda Island, Raja Island, Tamin Island, and Guratu Island. The study applied systematic sampling method that included collecting coral reef data using UPT (Underwater Photo Transect) method and coral fish data collection using visual census method. Study results showed that live coral coverage of reefs on the four small islands of Oba Sub-district had the highest value of 5.415% and the lowest value of 4.29%. There was positive relationship between coral growth form diversity and fish diversity. High diversity of coral growth forms was significantly related to high diversity of target reef fish.